Development of Animated Video Media About Students' Learning Interests at MTsT Daarut Tahfizh Al-Ikhlas - Imam Hamdani; Yuliana Nelisma; Tengku Febri Irwansyah (Suluh: Jurnal Bimbingan dan Konseling, 2025)
Animated video media that can increase students' interest in learning at MTsT Daarut Tahfizh Al-Ikhlas and to determine the effectiveness of its use in improving students' understanding of learning materials. Aim: This study aims to determine the feasibility, effectiveness, practicality, as well as student responses and the development of animated video learning media. Based on the formulation of the problem proposed, this study focuses on two main aspects, namely the development of animated video media and its effectiveness in increasing students' interest and understanding. Method: This study uses a research and development method (Research and Development) using the ADDIE model which stands for Analyze, Design, Development, Implementation, and Evaluation. Using descriptive analysis techniques using quantitative data. Data were collected through observation, questionnaires, and tests to measure students' interest in learning and understanding before and after using video media. Result and Discussions: The results of the study showed that the developed animated video media can attract students' attention and increase their interest in learning. In addition, the use of animated video media has proven effective in helping students understand learning materials better. Based on these findings, it is suggested that animated video media can be implemented more widely in the learning process to improve the quality of education and student learning outcomes. Conclusion: Thus, animated videos as an effective learning medium can increase students' interest in learning.